38.7k views
2 votes
Help this type of work confuses me

Help this type of work confuses me-example-1
User Adc
by
5.6k points

1 Answer

0 votes

Answer/Step-by-step explanation:

Given:

-x + 3x + 1 + 4(x + 2) = 54

To solve, first open the bracket by applying the distributive property. Multiply every term you have in the bracket by 4

-x + 3x + 1 + 4x + 8 = 54

Add like terms together

6x + 9 = 54

Subtract 9 from each side

6x = 54 - 9

6x = 45

Divide both sides by 6

x = 45/6

x = 7.5

User Shone
by
5.2k points